2013
DOI: 10.1007/s00268-013-2079-5
|View full text |Cite
|
Sign up to set email alerts
|

Amebic Acute Appendicitis: Systematic Review of 174 Cases

Abstract: Appendectomy specimens should be routinely sent for histopathologic examination. In the case of suspected amebic acute appendicitis, extra precautions-early appendectomy, metronidazole for antibiotic prophylaxis, wet-preparation examination, obtaining a timely pathology result, increasing the awareness of uncommon complications of appendectomy-can hasten appropriate therapeutic intervention and improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
(83 reference statements)
0
26
0
Order By: Relevance
“…One previous systematic review showed that preoperative diagnosis was established in only 3.0% of the patients (12). On the other hand, there are no epidemiological studies that used highly sensitive methods to detect E.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One previous systematic review showed that preoperative diagnosis was established in only 3.0% of the patients (12). On the other hand, there are no epidemiological studies that used highly sensitive methods to detect E.…”
Section: Discussionmentioning
confidence: 99%
“…Two review articles reported the clinical features of amoebic appendicitis (11, 12). The oversight of E.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not the issue in our case. Turkish authors obtained a total of 174 cases of amebic appendicitis using the PubMed and MEDLINE databases [7]. The mean age of the patients was 23.5 years (range 2 months-83 years).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, there may be a clinical course that varies from mild colitis and hemorrhagic dysentery to toxic megacolon, colon perforation and peritonitis. Perforation and peritonitis emerging as a result of fulminant colitis and intestinal necrosis are observed in 0.5% of patients and the mortality rate of these patients is above 40% (4). In a series of amebic appendicitis reported from Japan, postoperative intraabdominal severe complication rate reported as 37%, and the mortality rate reported as 25% (2).…”
Section: Amebiasis Is a Parasitic Infection Caused By Amoeba Called Ementioning
confidence: 99%